Altered Ex Vivo Expression of Caspase 8, Caspase 9, and Bcl-2 Is Associated with T-Cell Hyporeactivity in Patients with Paracoccidioidomycosis - Cacere, Camila R.; Mendes-Giannini, Maria José Soares [UNESP]; do Valle, Antonio Carlos F.; Duarte, Alberto J. S.; Benard, Gil (Amer Soc Microbiology, 2009)
To better understand the T-cell hyporesponsiveness of patients with paracoccidioidomycosis, we tested the hypothesis that the T cells were committed to apoptosis. We show here that T cells of patients with paracoccidioidomycosis overexpress caspase 9 and caspase 8 but express low Bcl-2 levels and that interleukin-2 was unable to revert the hyporesponsiveness. These data suggest that the T cells would in vivo be driven to a tolerant state and apoptosis.